"Gay" Image-Making from Britain and India: Sunil Gupta in the Late 1980s - Gregory Salter (British Art Studies)
This article explores Sunil Gupta's 1988 series *"Pretended" Family Relationships*, emphasising its focus on interracial relationships, to place it firmly in the context of the management of sexuality and race by the British state in the 1980s and to highlight the transnational histories and experiences to which it gestures, with a particular focus on India and gay and lesbian Asians in Britain. In doing so, it frames Gupta's practice as one of image-making with an interrogative approach to gay identity at this moment that surfaces a wide range of possibilities for building sexual lives and relationships in the process. The first section introduces the series and outlines its relationship to the uneven management of sexuality and race by the British state; the second turns to another series of images by Gupta, *Exiles* (1986), to address the transnational histories and fractured processes of recognition that underpinned his concern with the interracial a few years later; and the third turns back to *"Pretended" Family Relationships* to explore how the series is rooted in the complex navigation of family and personal life by gay and lesbian Asians in Britain. Across these sections, this article brings to the fore the particular interracial dynamics at the heart of Sunil Gupta's 1980s practice, noting in the process their overlaps and divergences with existing frameworks in queer studies, and putting forward a transnational and long-term history of Section 28, which has been under-articulated in art-historical and historical scholarship to date.